Knowledge, attitudes and practices among customers at pork butcheries in Kampala, Uganda - Heilmann, Martin; Roesel, Kristina; Clausen, Peter-Henning; Grace, Delia (Freie Universität Berlin, 2016)
Of all East African countries, Uganda boasts the highest pork consumption at 3.4 kg per capita per year (2011). Yet, there is little documentation how pork is produced, marketed and consumed, or on the implications this may have on public health. Up to 70% of produced pork is estimated to be consumed in urban/periurban areas mainly through informal butcheries and so-called pork joints, which are a combination of road-side butchery selling raw pork and a bistro for cooked pork often served with alcoholic drinks. This study was aimed at gaining better insight into this increasing pork business at the consumer level. Between June and July 2014, a baseline survey was conducted with 240 customers in 60 randomly selected pork butcheries in Kampala to assess their knowledge, attitudes and practices. Data was collected during face-to-face interviews by enumerators trained to conduct structured questionnaires in both English and the local language Luganda. Pork was most commonly purchased raw (48%), followed by fried (38%), roasted (9%) and cooked (5%). It was the second most common meat consumed at home after beef, followed by poultry, sheep, goat and fish. Pork was consumed on average 2.18 times per week. One third of households bought raw pork occasionally, while rates of “once per two weeks” (20%), “once a week” (20%), a few times a week (15%) or every day (15%) were also noted. Most (82%) customers ate their pork with raw and cooked vegetables, including matoke (59%), cassava (51%), tomatoes (9%), cabbage (5%), Irish potatoes (4%), onions (3%), greens (2%) and others. The main source of information for customers were television (68%), radio (29%), newspaper (15%), internet (10%), friends (9%), colleagues (2%) or others. Health aspects influenced the majority of respondents’ purchase decisions a lot (89%), while 9% stated “a bit” and 2% “not at all”. The high demand for pork along with the potential for cross contamination between raw pork and vegetables, indicates a food safety risk at not just pork butcheries but also at household level. Promotion of health aspects through public information channels can be used to influence purchase decisions and contribute to healthier clients and improved public health. This research was carried out with the financial support of the Federal Ministry for Economic Cooperation and Development, Germany, and the CGIAR Research Program on Agriculture for Nutrition and Health, led by the International Food Policy Research Institute, through the Safe Food, Fair Food project at ILRI.